Diversity of Collembola and Ground Surface Insects at Different Ages of Oil Palm Plantations (Elaeis guineensis Jacq.): Keanekaragaman Collembola dan Serangga Permukaan Tanah di Berbagai Umur Perkebunan Kelapa Sawit (Elaeis Guineensis Jacq.) - Putri, Kartika; Santi, Ratna; Aini, Sitti Nurul (Jurnal Ilmu Tanah dan Lingkungan, 2019)
The presence of Collembola and soil insects at different ages of oil palm plantations indicate the differences of soil qualities and fertility. The aims of this study was to know the diversity of Collembola and soil insects, age of palm oil plantations that have the highest diversity of Collembola and soil insects, and the relationship between diversity of Collembola and soil insects with soil C-organic content in palm oil plantations. The research was conducted in June-July 2018 at the oil palm plantation at Balunijuk Village, Bangka. Soil sample was taken from 3 year olds, 5 year olds and 13 year olds of oil palm plantation area. The identification of Collembola and soil insects was conducted in Microbiology Laboratory of Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung. This research used correlational descriptive method with survey technique. Sampling technique used was a purposive sampling technique. Collembola and soil surface insects were collected by using pitfall traps. The results showed that Collembola diversity and oil palm plantation insects were included in the moderate category. Plantation area of 3 years old was the area with the highest value (2.098). Positive correlation value between the diversity Collembola and soil insects with soil C-organic content, it means that increasing of diversity growth followed by increasing of C-organic content.